Integrative taxonomy study of brackish water crabs of the genus Ptychognathus Stimpson, 1858 (Crustacea: Brachyura: Varunidae) from Polynesia, with description of two new species - Mazancourt, Valentin De; Mazel, Virgile; Marquet, Gérard; Poupin, Joseph; Keith, Philippe (Zootaxa, 2024)
In the present contribution, five species of Ptychognathus Stimpson, 1858 are reported from Polynesia: P. crassimanus Finnegan, 1931, P. easteranus Rathbun, 1907, P. riedelii (A. Milne-Edwards, 1868) and two new species. The first new species named P. ngankeeae sp. nov. is close to P. barbatus (A. Milne-Edwards, 1873) from New Caledonia, which is here redescribed for comparison purposes. The second new species named P. similis sp. nov. is close to P. hachijoensis Sakai, 1955.